DENGAN SENGAJA TIDAK TAAT PERINTAH ATASAN OLEH PRAJURIT TNI - Ryan Maulana; Sutrisno (Reformasi Hukum Trisakti, 2023)
Giyanto committed the crime by willfully disobeying orders from superiors, and the issue at hand is whether the perpetrator's actions here complied with the law as set forth in the Book of Law 39 of 1997 concerning Military Criminal Law (KUHPM), as well as whether the judge's decision to impose a 6-month sentence plus an additional sentence was proper. This study use normative research methodologies, analyzes qualitative data, uses secondary data, and uses deductive reasoning to reach findings. The findings of the study and the discussion demonstrate that Giyanto is mindful of his decision to disobey or arbitrarily deviate from a superior's order. It follows that his activities satisfied the requirements for a crime as defined in Article 103(1) of the Military Criminal Code.